The Effectiveness of Snakes and Ladders Game Combined with Genially Application Student’s Passive Voice Mastery - Kamila, Meiliana Rahma; Mubarok, Husni (STIBA IEC JAKARTA, 2024)
This research aims to examine the effectiveness of the Snakes and Ladders game with the Genially application in students' passive voice mastery. This research used true experimental research design was employed, involving 70 eleventh-grade students from MAN 1 Jepara which divided in two classes, experimental and control classes. Pre-tests and post-tests were conducted to measure students' understanding and mastery of passive voice before and after treatment.The experimental group showed a significant improvement in their mastery of passive voice, with an average post-test score of 79.29, compared to the control group's average of 59.43. Statistical analysis using the independent sample t-test revealed a significant difference between the two groups (0,000< 0.05), indicating that the implementation of the Snakes and Ladders game with Genially was effective in improving students' learning outcomes.The research concludes that combining traditional games with modern educational technology, such as the Genially application, can effectively improve students' understanding in passive voice.